Immigration and Prostitution in Media Contents: a Diachronic Analysis around Building the “Other One” in Galician and Spanish Press - Puñal Rama, Ana Belén (Madrygal. Revista de Estudios Gallegos, 2017)
In the media, women are treated as the “Other Ones”, when compared to the standing role of the upper-middle-class white man and his positions of influence. But when talking about woman involved in prostitution, this gender discrimination brings together class discrimination and/or discrimination related to nationality, ethnicity or race, since prostitution and immigration are closely related both in the Spanish state and in Galicia. Previous studies on Communication and Gender considered as secondary the analysis of the intersection of gender discrimination and other types of discrimination. This communication will analyse press contribution to the construction of women involved in prostitution as the “Other Ones of the Other Ones”. The results have been obtained in two investigations, one at Galician level and another one adapted from the first into the Spanish state, based on the combination of content analysis and critical discourse analysis.
Keywords: Gender and Communication; Prostitution; Gender Roles; Sex discrimination.